RELATIONSHIP BETWEEN OXIDANT AND ANTIOXIDANT ENZYMES STATUS IN TYPE 2 DIABETIC PATIENTS WITH NEPHROPATHY IN SAUDI POPULATION. - Nagarajrao, Ramprasad; Alharbi, Samir Abdulkarim (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Oxidative stress has crucial role in pathogenesis of diabetic complications. Diabetic nephropathy (DN) is an important microvascular complication of diabetes and is widely recognized as the most common cause of the end-stage renal disease (ESRD) seen in clinical practice. Chemically, oxidative stress occurs as a result of increased levels of lipid peroxides and free radical intermediates, as well as a decrease in the total antioxidant capacity. This study analyzed the relationships between oxidant and antioxidant markers of DN in patients with type 2 diabetes mellitus (T2DM). Methods: A descriptive study was taken during the period from November 2016 to August 2017. The present study included 53 patients suffering from T2DM without nephropathy and 51 patients T2DM with nephropathy along with 69 age- and sex-matched healthy controls. Various biochemical parameters, antioxidant enzymes, and malondialdehyde (MDA) levels were measured and compared. Results: The glycosylated hemoglobin (HbA1c), urea, creatinine, microalbuminuria, and MDA levels were significantly increased (p<0.001), and antioxidant enzyme activities such as glutathione peroxidase (GPx), superoxide dismutase (SOD), and catalase (CTL) were significantly decreased (p<0.001) in T2DM with nephropathy patients followed by T2DM without nephropathy and control groups. There were a good negative correlations of HbA1c and GPx (r=âˆ’0.79), SOD (r=âˆ’0.61) and CTL (r=âˆ’0.74) (pâ‰¤0.05), whereas there was an excellent positive correlation of MDA concentration (r=0.85, pâ‰¤0.05) with HbA1c levels in diabetes with nephropathy. Conclusion: The study illustrated that, in diabetic patients, there is an increased concentration of lipid peroxides which may contribute to decreased levels of cellular antioxidant enzymes, further leading to T2DM with nephropathy. Hence, monitoring of these antioxidant enzymes and microalbuminuria parameters in the early stage of diabetic patients could be vital importance in possible preventing further development of complications. We suggest potential and new multiproperty antioxidants therapy as one of the most important treatment strategies for diabetic patients without nephropathy for the prevention and slowing of diabetic with nephropathy before reaching to ESRD.